Pengamanan Data Pasien Di UPT. Puskesmas Pujon Kalimantan Tengah Menggunakan Kriptografi Super Enkripsi - Falensky, Lee Valdho; Pakereng, Magdalena A. Ineke (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
Along with the development of information and communication technology nowaday, data security in exchanging information is increasingly important. One technique that can be used to secure the data is super encryption cryptography. Super encryption is a cryptographic technique that combines two or more algorithms. In this research, the encryption decryption process data text of patient biodata of Technical Implementation Unit Pujon Health Center Central Kalimantan was conducted using three cryptography, namely Columnar Transposition, Vigenere Cipher and Monoalphabetic. The result of this research is that the super encryption that has been built can encode (encrypt) and return (decrypt) messages in text. data text of patient biodata of Technical Implementation Unit Pujon Health Center Central Kalimantan tested, before decryption encryption and after decryption encryption did not change the number of characters. The number of characters does not affect the speed of the process because the number of characters used can produce the same processing speed